Labio-facial Necrotizing Fasciitis in a Young Patient - Lança, Maria Leticia de Almeida [UNESP]; Trento, Guilherme Dos Santos; Santos, José Cleveilton Dos; Navarro, Claudia Maria; Pereira-Filho, Valfrido Antônio (Wolters Kluwer, 2021)
ABSTRACT: Necrotizing fasciitis (NF) is an infection of the deeper tissues that results in progressive destruction of muscle fascia and overlying subcutaneous fat. It has a fast and destructive course. Moreover, it is related to immunosuppression and could be fatal. The aim of this study is to report a clinical case of a young patient, without immunosuppression, who developed NF evolution due to an erroneous diagnosis of abscess at the beginning of the disease. Patient was submitted to broad-spectrum antibiotic therapy and aggressive surgical treatment. Adequate treatment led to a satisfactory evolution in a short period of time. Early recognition and adequate treatment are essential for a favorable prognosis.